2016
DOI: 10.1007/s00253-016-7640-3
|View full text |Cite
|
Sign up to set email alerts
|

Targeting asparagine and autophagy for pulmonary adenocarcinoma therapy

Abstract: The mounting number of patients with pulmonary adenocarcinoma (ADCA) is subjected to poor prognosis and heavy mortality, which prompts us to explore new potential therapeutics for lung ADCA. Herein, we reported a novel approach for lung ADCA therapy by abolishing autophagy and asparagine. We demonstrated that deprivation of asparagine by asparaginase could induce significant cytotoxicity and apoptosis in A549 and H1975 cells. During this process, autophagy was triggered by the asparaginase treatment, character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Asparaginase has been approved for treatment of childhood ALL by FDA for more than 40 years. Recent studies revealed that asparaginase could be used as a chemotherapeutic agent against not only ALL but also other types of leukemia and several malignant solid cancers [ 18 26 ]. In addition, several literature has reported the anti-tumor effect of asparaginase on glioblastoma [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Asparaginase has been approved for treatment of childhood ALL by FDA for more than 40 years. Recent studies revealed that asparaginase could be used as a chemotherapeutic agent against not only ALL but also other types of leukemia and several malignant solid cancers [ 18 26 ]. In addition, several literature has reported the anti-tumor effect of asparaginase on glioblastoma [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, L-asparagine is an essential amino acid for cancer cell growth, and asparagine depletion has become one of the most promising strategies for cancer therapy [ 15 17 ]. Except for being proved for treatment of ALL, asparaginase is also reported to be effective in treatment of other kinds of leukemia including non-Hodgkin’s lymphoma [ 18 ], acute myelocytic leukemia (AML) [ 19 , 20 ], chronic myelocytic leukemia (CML) [ 21 ], chronic lymphocytic leukemia (CLL) and several malignant solid cancers such as melanosarcoma [ 22 , 23 ], ovarian cancer [ 24 , 25 ] and pulmonary adenocarcinoma (ADCA) [ 26 ]. Recent study reported that depletion of asparagine by asparaginase sensitized GBM cells to apoptosis in vitro and in vivo [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Samples were examined with a JEM 1400 transmission electron microscope (JEOL, Inc., Peabody, MA, USA) at 80 kV.…”
Section: Methodsmentioning
confidence: 99%
“…Since asparagine is a downstream metabolite of glutamine, combined inhibition of GLS1 with asparagine deprivation is synthetically lethal for solid tumor cells (Li et al , ). Notably, asparaginase treatment is also effective for solid tumors, when combined with inhibition of autophagy (Zhang et al , ; Li et al , ).…”
Section: Introductionmentioning
confidence: 99%